Sink Location Protection Protocols Based on Packet Sending Rate Adjustment. (10th January 2016) - Chen, Juan; Lin, Zhengkui; Liu, Yan; Hu, Ying; Du, Xiaojiang
Sink location protection is critical to the viability of sensor networks as the central point of failure. Most existing work related to sink location protection focuses on local traffic analysis attack. In this paper, we study the sink location protection problem under a more powerful type of attack, the global traffic analysis attack. In order to hide the sink location, a protocol based on packet sending rate adjustment (SRA) is proposed. By controlling the packet sending rate of each node according to the current number of source nodes, SRA conceals the real traffic volume generated by source nodes and hence disguises the location of the sink. For further reducing the communication cost, we propose a light weight SRA protocol (L-SRA), which protects the sink location while significantly decreasing the communication cost. Performance of both SRA and L-SRA has been validated by theoretical analysis and simulation results.